How Emotion Labor Shapes English Teacher Identity in Underfunded Universities of the Global South: A Case Study of Professional Struggles and Resilience - Morteza Amirsheibani; Sevinch Xolova (International Journal of Educational Research & Social Sciences, 2026)
This study deals with the emotional labor and identity construction of teachers of English at underfunded public universities in Tashkent, Uzbekistan. The study adopts a narrative inquiry, seeking to discover how teachers deal with their emotional realities in the absence of any material or expressive support from the institution. Eight teachers (five females and three males) between the ages of 29 and 52, participated in two semi-structured interviews over a month and kept weekly reflective journals. The thematic narratives indicated three major patterns: strategically suppressing emotions as a means of professional self-preservation, lack of institutional recognition whereby identity erodes, and in the end, emerging emotional resilience attributed to some forms of student interaction and collegiality. Findings indicate that the dimension of emotion is centrally positioned in the formative process of a professional identity and that, therefore, the higher education institution’s curricular reforms have to integrate these dimensions if the development of teachers has to be a long-term process.